ANALISIS STRATEGI PENGEMBANGAN BISNIS UMKM WARTEG SEKITAR KAMPUS IBI KOSGORO 1957 JAKARTA - Andriyanty, Reny (Mediastima, 2021)
Warteg is a food business based on rice and side dishes, which is Indonesia typish. The purpose of this research is to be able to formulate the spesific business strategy for the development of the warteg business around the IBI Kosgoro Campus 1957, South Jakarta. The research method is descriptive qualitative with data analysis methods applying SWOT analysis. The study recommend three strategies, namely: 1) providing hygienic and comfortable place, full music and television and food security-license, longer operating hours, 2) providing a fresh and varied menu every day and 3) setting low prices which are supported by digital payment technology applications